Gestão financeira de sistemas leiteiros na região oeste do Paraná - Zimpel, Roney (2014)
The objective of the present study was to identify producers who adopt financial management practices in Dairy Production Systems (SPL's) according to socioeconomic and productive variables. Additionally, those were compared with dairy farmers who do not adopt financial management practices. In order to that 55 semi-structured questionnaires were applied to the milk producers in the Western region of Paraná State. The questionnaires were conducted between September 2013 and April 2014. Data were tabulated and submitted to descriptive and multivariate statistical analysis. The techniques of clustering and exploratory factor analysis were employed. Two groups were defined from variables related to the practice of financial management. The first one was formed by dairy farmers who do not adopt financial management practices in SPL's (N= 49) and the second one by producers who adopt financial management practices in SPL's (N= 6). Between the groups ignificant statistical difference (p<0.05) was found among the variables that defined them: The use of tools for financial control; use of software for financial control and cash flow realization. In a second step, the mean test was performed and equal ratio test for a set of socio-productive variables. For those, no statistical difference between groups was found. In the following analysis, from the socioeconomic and productive variables, three factors by AFE were defined. The first factor was defined by structural variables (F1); the second by socioeconomic variables (F2) and the third by variable information (F3). The first factor explained 26% of the total variance, being therefore the one that most differentiate producers analyzed. From these factors, producer groups defined by cluster analysis were plotted on graphics with two dimensions. It could be concluded that producers who perform financial management practices (Group 2) own lower productive structures, lower value for social variables and greater financial management information SPL